Cultivation practices and soil water storage effects on grain yield and quality of winter wheat in the Loess Plateau, China - Ding, Pengcheng; Noor, Hafeez; Li, Xiaofen; Xing, Jun; Yan, Yongqiang; Guo, Wendi; Ren, Aixia; Li, Linghong; Ren, Yongkang; Sun, Min; Gao, Zhiqiang (Frontiers in Plant Science, 2026)
IntroductionIn the water-limited Loess Plateau of China, wheat productivity faces severe constraints. This study investigates the physiological and quality determinants of yield and protein content across multiple winter wheat cultivars to identify key breeding targets for dryland systems.MethodsEleven cultivars were analyzed for soil water storage dynamics, dry matter accumulation and translocation, nitrogen use efficiency, and grain quality parameters, including volatile flavor compounds.ResultsHigh yield potential was driven by superior pre-anthesis nitrogen assimilation and substantial post-anthesis dry matter remobilization. The highest-yielding cultivar (YH-805) achieved this through a greater number of grains per spike. Conversely, higher grain protein content (e.g., in YH-618) was linked to enhanced post-flowering nitrogen translocation. A fundamental yield–protein trade-off was confirmed. The medium-yield, high-protein cultivar YH-115 exhibited the most favorable flavor profile, associated with key volatile compounds like octanal and hexanal.DiscussionThe results demonstrate that yield and quality are governed by distinct pre- and post-anthesis resource allocation strategies. Targeted breeding for specific traits—such as pre-anthesis nitrogen uptake for yield or post-anthesis nitrogen translocation for protein—can help optimize for either enhanced productivity or superior end-use quality in dryland wheat systems.